If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = x + 3 Reorder the terms: 16 = 3 + x Solving 16 = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 16 + -1x = 3 + x + -1x Combine like terms: x + -1x = 0 16 + -1x = 3 + 0 16 + -1x = 3 Add '-16' to each side of the equation. 16 + -16 + -1x = 3 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = 3 + -16 -1x = 3 + -16 Combine like terms: 3 + -16 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 5q-7=23 | | 4=19+5x | | -2x+x=6 | | 2x+4=5-3x | | 8(3x+1)=7(2x+12) | | 6+2(5-2a)=2a(2+8) | | (2m+1)(3m-5)=0 | | 37=-43n | | 16+(9+(-5))= | | -a=12a-65 | | -15(h-2)= | | 5x+3+3x=9x+3-x | | 2.95x+5.95(90-x)=405 | | -t+4=873 | | -t+4= | | 4-5+x-(-1)=5 | | -2+4x=-23 | | 5x^2y^2+9xy-2=0 | | 12x^3-13xy-14y^2=0 | | 8-2(2x+1)=3(x-5) | | 10+(9+(-7))= | | 14-8=e | | -.3(.7x-.9)=-1.83 | | 12*p=3 | | 2.3x-9=1.2 | | 24x=40 | | m+-6+-1=-9 | | 12x+376=280+15x | | 25h-50=250 | | x-(-5)+2=9 | | 3(3y+3)-7y=15 | | (2/3)-(2w+2/5)=2-(w+16/6) |